2018
DOI: 10.1371/journal.ppat.1007323
|View full text |Cite
|
Sign up to set email alerts
|

Independent amplification of co-infected long incubation period low conversion efficiency prion strains

Abstract: Prion diseases are caused by a misfolded isoform of the prion protein, PrPSc. Prion strains are hypothesized to be encoded by strain-specific conformations of PrPSc and prions can interfere with each other when a long-incubation period strain (i.e. blocking strain) inhibits the conversion of a short-incubation period strain (i.e. non-blocking). Prion strain interference influences prion strain dynamics and the emergence of a strain from a mixture; however, it is unknown if two long-incubation period strains ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 72 publications
1
10
0
Order By: Relevance
“…3). These data suggest that soil-bound PrP Sc can compete for PrP C , which is thought to be the limiting factor in strain interference (43, 49). We hypothesize that the PrP C binding site on PrP Sc is different from the site at which PrP Sc binds to the soil surface, allowing adequate conversion activity during the initial round of PMCAsi, when PrP Sc exists largely in the adsorbed state (50, 51).…”
Section: Discussionmentioning
confidence: 95%
“…3). These data suggest that soil-bound PrP Sc can compete for PrP C , which is thought to be the limiting factor in strain interference (43, 49). We hypothesize that the PrP C binding site on PrP Sc is different from the site at which PrP Sc binds to the soil surface, allowing adequate conversion activity during the initial round of PMCAsi, when PrP Sc exists largely in the adsorbed state (50, 51).…”
Section: Discussionmentioning
confidence: 95%
“…The delayed disease then usually has the clinical presentation and PrP Sc of the faster strain. Alternatively, mixed infections can result in independent replication of both strains 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that certain combinations of strain do not compete, and animals have the pathology and PrP Sc of the shorter incubation strain without delay in incubation periods 35 37 . In addition, the two coinfecting strains can replicate independently, where an animal has the pathology of the shorter incubation strain without delay, but PrP Sc is a mixture of both strains 23 , 36 38 .…”
Section: Introductionmentioning
confidence: 99%
“…Pre‐infecting mice with a slow‐incubating strain could severely delay or completely block subsequent infection by a fast strain. Bessen, Bartz and colleagues reported similar findings in golden Syrian hamsters (Bartz et al ., ; Eckland et al ., ). It was argued that the blockage in propagation was not immunological in origin but was caused by competition for resources at a common replication site.…”
Section: Introductionmentioning
confidence: 97%